2005
DOI: 10.1063/1.2137466
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrical properties of ferroelectric thin films by ultraviolet radiation

Abstract: Ferroelectric films in the paraelectric phase exhibit two undesirable properties: hysteresis in the voltage-capacitance characteristics and a significant relaxation time of the capacitance. Our experiments show that suppression of both of these is achieved by using UV radiation with wavelengths corresponding to the material forbidden gap. Experimentally we also observed UV radiation induced modulation of thin film permittivity without an applied electric field. The observed phenomena are believed to have the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…where a i are numerical constants (dependent on C 1 , C 2 ) evaluated via numerical integration over loop momenta. We consider ten sets of different values for the Symanzik coefficients, corresponding to the most commonly used actions, shown in Table I: The plaquette action, the tree-level Symanzik improved action, the Lüscher-Weisz tadpole improved actions (TILW), the Iwasaki action and the DBW2 action (see [12][13][14][15][16][17]). The quantities a i , for each one of the ten sets of parameters, are presented in Table II.…”
Section: Computation and Resultsmentioning
confidence: 99%
“…where a i are numerical constants (dependent on C 1 , C 2 ) evaluated via numerical integration over loop momenta. We consider ten sets of different values for the Symanzik coefficients, corresponding to the most commonly used actions, shown in Table I: The plaquette action, the tree-level Symanzik improved action, the Lüscher-Weisz tadpole improved actions (TILW), the Iwasaki action and the DBW2 action (see [12][13][14][15][16][17]). The quantities a i , for each one of the ten sets of parameters, are presented in Table II.…”
Section: Computation and Resultsmentioning
confidence: 99%
“…Besides the fast response process ͑soft mode response, Ͻ1 ns͒, there are slowrelaxation processes, which cause up to 10% of the capacitance value to relax ͑i.e., return to initial state after the pulse duration͒ for a time ϳ 10 3 s. [5][6][7] This phenomenon is schematically presented in Fig. 9 In, 10 it was demonstrated that a way to suppress the slow-relaxation processes is irradiating the sample with UV light. This could cause a significant reduction in the efficiency of the capacitors tuning under unipolar pulse control voltages.…”
Section: Effect Of Ultraviolet Radiation On Slow-relaxation Processesmentioning
confidence: 99%
“…30 The presence of the oxygen vacancies, in particular, may result in the hysteresis behavior of the field dependence of permittivity. 31,32 The analysis of the dielectric response of our samples shows that the hysteresis phenomenon is well pronounced in the BSTO films grown at low temperatures and diminishes gradually with growth temperature in the whole temperature range. For example, Fig.…”
Section: Dielectric Responsementioning
confidence: 99%